Mechanical properties and fracture behaviour of coconut fibre-based green composites - Alida, Abdullah; Shamsul Baharin, Jamaludin, Prof. Dr.; Mazlee, Mohd Noor; Kamarudin, Hussin, Brig. Jen. Dato' Prof. Dr. (Foundation for Materials Science and Engineering “Serban Solacolu”, 2013)
Link to publisher's homepage at http://solacolu.chim.upb.ro/